Life Review Therapy (Melidupa) Effective to Increase the Sexual Quality of Life of Elderly Women in Banjar Gelumpang, Sukawati Village - Ni Kadek Emmawati; IGA Ratih Agustini; IGAA Sherlyna Prihandhani; Desak Putu Muliani Purnama Dewi (Nursing and Health Sciences Journal (NHSJ), 2022)
The Elderly are often faced with problem, one of which is decreasing sexual function to 86%, this can lead to decrease in sexual quality of life elderly. The low quality of sexual life can affect their health thereby increasing the burden of family dependency. One of the treatments to improve the sexual quality of life is by giving life review therapy which is a therapy for telling stories of past experiences. This study aims to determine the effect of life review therapy on the sexual quality of life in elderly women. This study uses Quasi-Experimental, a one-group pretest-posttest design for the elderly which are aged 60-74 years. Collecting data using the SQOL-F questionnaire. The results of the pretest showed that the majority of the elderly's sexual quality of life was low at 14 (66.7%). The majority of post-test results have a good sexual quality of life 16 (76.2%). There is a difference in the sexual quality of life between the pretest and posttest p-value = 0.001 (α <0.05). It can be concluded that there is an effect of life review therapy on the sexual quality of life in elderly women in Banjar Gelumpang, Sukawati Village.